The effects of kinesthetic and visual motor imagery on interjoint coordination in the hemiplegic index finger: an experimental study using the index of temporal coordination/ Os efeitos da imagem cinestésica e viso-motora na coordenação interfalângica do dedo indicador hemiplégico: um estudo experimental usando o “the index of temporal coordination” - O’Brien, Jonathon; Bracewell, Robert Martyn; Castillo, Juan Alberto (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Upper limb hemiparesis is a common impairment following stroke and can affect interjoint coordination. Motor imagery training is one treatment strategy. However, motor imagery can use visual or kinesthetic modalities and there has been a lack of research comparing the effectiveness of these modalities when treating the upper limb. The aim of this study was to compare visual and kinesthetic motor imagery in improving interjoint coordination in the hemiparetic index finger. Fifteen stroke survivors with upper limb hemiparesis were allocated to groups using kinesthetic or visual motor imagery, or a control group using guided relaxation. Reaching and grasping movements of the upper limb were captured using optoelectronic motion capture. Interjoint coordination of the hemiparetic index finger was analysed using the index of temporal coordination. No significant differences were found for interjoint coordination following treatment in either condition. Future work should focus on comparing kinesthetic and visual motor imagery in the rehabilitation of more proximal upper limb joints.